RETRACTED : The Influence of Service Quality, Brand Image and Customer Relationship Management on Indomaret Customer Loyalty Padurenan Village, East Bekasi - Muhammad Lutfi Rizaldi; Resti Hardini; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the influence of service quality, brand image and customer relationship management to customer loyalty. This research is conducted by using the primary data of multiple linear equations of customer loyalty is LP = 3.346 + 0.338 KP + 0.298 BI + 0.222 CRM. Testing statistical model of F customer loyalty test obtained with Fcount of 32,271 with value of sig 0,000 which mean value of service quality, brand image and customer relationship management have positive and significant influence to customer loyalty. Test T customer loyalty obtained service quality of 3,337 with value of sig 0,001 <0,05, brand image equal to 3,363 with value of sig 0,001 <0,05, and customer relationship management equal to 2,802 with value of sig 0,006 <0,05 meaning service quality, Brand image and customer relationship management have a positive and significant impact on customer loyalty. The value of determination coefficient (R2) customer loyalty equal to 0,502 or 50,2% improvement of customer loyalty variable can be explained by service quality variable, brand image and customer relationship management the rest 49,8% explained other variable not enter into this research.